THE EFFECT OF ONLINE STORE DESIGN QUALITY ON CONSUMER PURCHASING DECISIONS - Santi Budiman; Parama Kartika Dewa (International Journal Management and Economic, 2026)
The purpose of this research is to enable online stores to develop effective strategies in focusing on the development of their existing design quality to ensure their platforms can maintain customer loyalty, encourage customers to make purchases, and generate other positive effects. The model in this study has a stage, namely design quality, which consists of usability, functionality, and sociability factors to shape purchasing decisions. Sampling was conducted using non-probability sampling and purposive sampling techniques with a sample size of 230 respondents. The criteria set for the sample were respondents who had made purchases at online stores within the last year. The questionnaire was distributed online to all respondents in the Special Region of Yogyakarta Province to meet data collection requirements. This study used multiple regression analysis processed with SPSS for Mac software. In general, the results of this study indicate that the variables of usefulness, functionality, and sociability have a positive effect on the variable of purchasing decision. The implication for online stores is to develop strategies to ensure that the quality of their platform design can trigger consumers to make purchases and even spread other positive effects, in line with the main objective of this study.